2011
DOI: 10.1063/1.3633952
|View full text |Cite
|
Sign up to set email alerts
|

TRIPLE Q: A three channel quantum cascade laser absorption spectrometer for fast multiple species concentration measurements

Abstract: A compact and transportable three channel quantum cascade laser system (TRIPLE Q) based on mid-infrared absorption spectroscopy has been developed for time-resolved plasma diagnostics. The TRIPLE Q spectrometer encompasses three independently controlled quantum cascade lasers (QCLs), which can be used for chemical sensing, particularly for gas phase analysis of plasmas. All three QCLs are operated in the intra-pulse mode with typical pulse lengths of the order of 150 ns. Using a multiplexed detection, a time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…With such an approach combinations of three [9] or even four [10] QCLs were realized at the expense of increased optical complexity, complicated and sensitive alignment, bulky instrumental setups and higher overall costs.…”
Section: Introductionmentioning
confidence: 99%
“…With such an approach combinations of three [9] or even four [10] QCLs were realized at the expense of increased optical complexity, complicated and sensitive alignment, bulky instrumental setups and higher overall costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this case, the choice of the broadband laser source is justified by the fact that the broad and quasi-structureless propane absorption spectrum does not require high spectral resolution, and at the same time, for leak-detection, a precise and fast "on-off" decision without a detailed spectral analysis is fully sufficient. Yet, the low spectral resolution brings several advantages over interpulse or intrapulse tunable diode laser absorption spectroscopy techniques typically employed for high sensitivity trace gas measurements [16][17][18][19][20]. First, the broadband laser signal, which is spectrally matched to the propane absorption features, gives us the possibility to perform the measurement in one shot without wavelength scanning, thus gaining at speed.…”
Section: B Selection Of the Laser Sourcementioning
confidence: 99%
“…Using time resolved quantum cascade laser absorption spectroscopy, the densities of NO, NO2 and N2O have been measured in synthetic air as well as in air with 0.8% of NO2 or N2O. Figure 12 shows a schematic sketch of the experimental set-up consisting of a closed tube reactor made of Pyrex and a 3 channel QCLAS spectrometer, TRIPLE Q [15]. This study showed that IR titration coupled with QCLAS is a reliable technique for the determination of the quenching probability of vibrationally excited nitrogen molecules on a wide range of materials relevant to plasma technology.…”
Section: Kinetic Studies Of No Formation In Pulsed Air-like Low-pressmentioning
confidence: 99%
“…Using time resolved quantum cascade laser absorption spectroscopy, the densities of NO, NO 2 and N 2 O have been measured in synthetic air as well as in air with 0.8% of NO 2 or N 2 O. Figure 12 shows a schematic sketch of the experimental set-up consisting of a closed tube reactor made of Pyrex and a 3 channel QCLAS spectrometer, TRIPLE Q [15].…”
Section: Kinetic Studies Of No Formation In Pulsed Air-like Low-pressmentioning
confidence: 99%
See 1 more Smart Citation